The design of mobile social application for children with autism - Azahari, I.N.N.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Autism is a neural syndrome that complicates the growth of mind, producing challenging result in communicating, social interaction, and impairment in behaviour. Since there is no cure for autism, prompt interventions and effective educational exercises allow children to achieve massive improvement. During the teaching and learning process, children with autism require particular consideration and attention. Thus, with the implementation of information technology in special education, the teaching and learning process could to become more efficient. Struggle in social interaction skill is known as one of the main drawback encountered by children with autism. Therefore, a mobile social application is proposed to help the children to develop social interaction skills. Nonetheless, this paper only deliberates on the design phase mobile application development. It is developed for children with medium functioning Autism Spectrum Disorder (ASD) who are learning basic interaction skills. The application's design phase implements the results from the analysis phase, which has concluded earlier. Five evaluators were involved in the heuristic evaluation, in order to enhance the user interface of the mobile social application. The outcomes from the evaluation conclude that all evaluators has agreed with all heuristics. Not to mention, beneficial recommendations were also achieved from the evaluation. The future work of this paper will be the development phase of the mobile social application. Â© 2016 IEEE.